2016
DOI: 10.1097/inf.0000000000001322
|View full text |Cite
|
Sign up to set email alerts
|

Single-dose Universal Hepatitis A Immunization in One-year-old Children in Argentina

Abstract: Single-dose universal hepatitis A immunization in 1-year-old children resulted in sustained immunologic protection for up to 9 years in Argentina. These findings, along with the low current disease burden, confirm the success of the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 26 publications
1
11
1
Order By: Relevance
“…protein crosslinking with formalin) sufficiently disrupts the dense repetitive array of their surface epitopes to ablate their “virus-like” character [55] . An exception may be the Hepatitis A (HAV) inactivated virus vaccine, which appears to induce durable protective antibody responses after a single dose and therefore may retain a sufficient number of repetitive surface epitopes after inactivation to retain its virus-like character [56] . On the other hand, the observation that live attenuated vaccines, such as yellow fever and vaccinia, induce potent, durable antibody responses and immunity to infection after the primary inoculation in most vaccinees [57] has usually been attributed to the infectious nature of the inoculum.…”
Section: Immunologic Considerationsmentioning
confidence: 99%
“…protein crosslinking with formalin) sufficiently disrupts the dense repetitive array of their surface epitopes to ablate their “virus-like” character [55] . An exception may be the Hepatitis A (HAV) inactivated virus vaccine, which appears to induce durable protective antibody responses after a single dose and therefore may retain a sufficient number of repetitive surface epitopes after inactivation to retain its virus-like character [56] . On the other hand, the observation that live attenuated vaccines, such as yellow fever and vaccinia, induce potent, durable antibody responses and immunity to infection after the primary inoculation in most vaccinees [57] has usually been attributed to the infectious nature of the inoculum.…”
Section: Immunologic Considerationsmentioning
confidence: 99%
“…Following the advice of the Chilean Society of Infectology [ 16 ], which was prompted by the current outbreak, a single dose of inactivated HAV vaccine for all infants at age 18 months has been incorporated to the Chilean Universal Expanded Immunization Programme. The programme considers a local cost-effectiveness analysis [ 17 ] and the good results of single dose immunisation in children in Latin America [ 18 , 19 ]. We hope that in the long term this public health intervention will protect the future generations from outbreaks like the one we are now experiencing.…”
Section: Discussionmentioning
confidence: 99%
“…7 Argentina was the first country (in June 2005) to implement vaccination with a one-dose HepA-I schedule, and surveillance data proved the dramatic decrease in hepatitis A incidence in the country. 58 The effectiveness of a one-dose schedule has also been verified in Brazil, where UCVP was conducted since August 2014. 92 In 2012, the WHO position paper on hepatitis A vaccines suggested that national vaccination programs might consider the inclusion of single-dose HepA-I in vaccination schedules.…”
Section: Universal Childhood Vaccination Program (Ucvp) Against Hepatmentioning
confidence: 98%
“…Studies concerning the long-term duration of anti-HAV following single-dose of HepA are rare for both HepA-I and HepA-L. A study found that a single dose of HepA resulted in sustained immunologic protection for up to 9 y among 1-y-old children in Argentina. 58 A Chinese study found that at 15 y postvaccination with a single dose of HepA-L, the seropositive rate of anti-HAV was still very high (81.3%) among children. 59 In another Chinese study, a similar persistence of anti-HAV postvaccination was detected between one-dose of HepA-L and one-dose of HepA-I among children, but the follow-up time was only 5 y postvaccination.…”
Section: Immunogenicity Following Hepa Vaccinationmentioning
confidence: 99%